2022
DOI: 10.1177/24741264221083873
|View full text |Cite
|
Sign up to set email alerts
|

Optical Coherence Tomography Angiography in Pediatric Retinal Disorders

Abstract: Purpose: The rapid and noninvasive nature of optical coherence tomography angiography (OCTA) makes it a potentially valuable tool for imaging the retina in children. With the optimization of tabletop systems and the development of experimental handheld OCTA devices, there is expanded potential for OCTA in the clinic and the operating room. This article reviews the utility of OCTA in some of the most common pediatric retinal disorders. Methods: A thorough computerized PubMed search was performed to review relev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…An exciting area of future OCTA research revolves around the development of portable and handheld OCT and OCTA technology. Recently, multiple groups have demonstrated the ability to capture high‐quality OCTA images with investigational portable and handheld OCTA devices in infants, including those with ROP (Campbell et al., 2017; Hsu et al., 2019; Kothari et al., 2020; Moshiri et al., 2019; Ponugoti et al., 2022; Song et al., 2019; Viehland et al., 2019; Vinekar et al., 2016). The development of such technology will allow for the longitudinal analysis of vascular development in infants with ROP.…”
Section: Discussionmentioning
confidence: 99%
“…An exciting area of future OCTA research revolves around the development of portable and handheld OCT and OCTA technology. Recently, multiple groups have demonstrated the ability to capture high‐quality OCTA images with investigational portable and handheld OCTA devices in infants, including those with ROP (Campbell et al., 2017; Hsu et al., 2019; Kothari et al., 2020; Moshiri et al., 2019; Ponugoti et al., 2022; Song et al., 2019; Viehland et al., 2019; Vinekar et al., 2016). The development of such technology will allow for the longitudinal analysis of vascular development in infants with ROP.…”
Section: Discussionmentioning
confidence: 99%
“…Hsu et al reported a series of 11 eyes of 6 patients with FEVR imaged with OCTA, which showed dilation, disorganization, straightening, heterogeneous vessel density and curls formation in SCP [ 67 ]. Decreased vessel density, disorganization of vessels, curls/loops and a specific finding of end-bulbs in 7 out of 11 eyes were noted in the DCP of an FEVR patient [ 10 , 67 ]. These findings were minimal on traditional fluorescein angiography.…”
Section: Oct and Octa In Retinal Vascular Diseasesmentioning
confidence: 99%
“…However, it is important to note that subretinal exudate may lead to obscuration of choriocapillaris (CC), and manual segmentation of OCTA images in a patient with macula exudates may be required to accurately visualize blood vessels [ 84 , 85 ]. In addition, OCTA of Coats disease may also reveal an irregular FAZ with crossing vessels on both the SCP and DCP [ 10 ]. A study performed by Cennamo et al regarding treatment response monitoring using OCT and OCTA after serial intravitreal anti-VEGF in Coats disease in 15 eyes in 15 patients with a mean age of 20.4 ± 2 years also showed subretinal exudates persisted in the macular region and generalized vascular rarefaction was still noted in the SCP, DCP and CC [ 85 ].…”
Section: Oct and Octa In Retinal Vascular Diseasesmentioning
confidence: 99%
See 1 more Smart Citation